DEVELOPMENT OF SMART ROUTE GAME MEDIA TO IMPROVE STUDENTS' COGNITIVE ABILITIES IN THE SUBJECT OF ISLAMIC CULTURE AND HISTORY IN CLASS VII MTS SYI'AR ISLAM - Nurul Laela; Rr Kusuma Dwi Nur Ma’rifati (Jurnal Bilqolam Pendidikan Islam, 2026)
A common problem in Islamic Cultural History (ISCR) teaching is the low cognitive abilities of students due to the use of conventional learning methods that do not actively involve students in the learning process. This condition causes students to tend to be passive, unenthusiastic, and have difficulty understanding the material in depth. In response to this phenomenon, this study aims to initiate the development of game-based learning media through the Smart Route Game and to determine the effect of its use on improving students' cognitive abilities. The research method applied is Research and Development (R&D) with a 4D model that includes the Define, Design, Develop, and Disseminate stages, which in its implementation is limited to the Develop phase. This study involved 25 seventh-grade students at MTs Syiar Islam Maibit as trial subjects. Data collection instruments included tests, questionnaires, observations, and interviews, with data analysis techniques using descriptive statistics and N-gain calculations. The results indicate that the Smart Route Game media is categorized as very suitable for use, referring to the validation score from material experts of 88.6% and media experts of 97.9% after going through the revision stage. Furthermore, there was a significant increase in the average student score from 64.88 to 85.2, indicating an effective improvement in cognitive abilities. The positive response from users (teachers and students) also reinforces the conclusion that the Smart Route Game is an interactive learning tool capable of creating a more interactive and enjoyable learning environment and enhancing students' cognitive abilities in the subject of Islamic Cultural History.